2013
DOI: 10.4049/jimmunol.1201469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IgA Constant Domain on HIV-1 Neutralizing Function of Monoclonal Antibody F425A1g8

Abstract: With the majority of HIV infections resulting from mucosal transmission, induction of an effective mucosal immune response is thought to be pivotal in preventing transmission. HIV-specific IgA, but not IgG, has been detected in genital tract, seminal fluid, urethral swabs, urine and vaginal wash samples of HIV-negative sex workers and HIV-status discordant couples. Purified mucosal and plasma IgA from some individuals with highly exposed, persistently sero-negative (HEPS) can neutralize infection and present c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
3
20
2
Order By: Relevance
“…For this reason, we produced selected bNAbs as recombinant IgG and IgA1/IgA2 monoclonal antibodies. In contrast to what was reported in previous works, 46,54,55 we showed that swapping the bNAbs' Fc region from IgG to IgA did not substantially modify or alter their affinities, targeted epitopes or antiviral inhibitory activities. When applied with or without virus at the surface of the epithelial monolayers, we observed that a similar fraction of purified IgG and IgA was transported to the basal pole, likely in a FcRn-independent manner.…”
Section: Discussioncontrasting
confidence: 99%
“…For this reason, we produced selected bNAbs as recombinant IgG and IgA1/IgA2 monoclonal antibodies. In contrast to what was reported in previous works, 46,54,55 we showed that swapping the bNAbs' Fc region from IgG to IgA did not substantially modify or alter their affinities, targeted epitopes or antiviral inhibitory activities. When applied with or without virus at the surface of the epithelial monolayers, we observed that a similar fraction of purified IgG and IgA was transported to the basal pole, likely in a FcRn-independent manner.…”
Section: Discussioncontrasting
confidence: 99%
“…Monomeric MAb362 IgA1 was also co-expressed with J chain to produce dimeric IgA, which further improved neutralization ( Figure 4b ). This is consistent with our prior study showing isotype switch to IgA1 lead to improved antibody neutralization of HIV infection 25 Our data extends this observation to coronavirus, suggesting that IgA may play an important role in SARS-CoV-2 neutralization.…”
Section: Resultssupporting
confidence: 93%
“…While some reports have characterized the advantage of using nanoparticles to encapsulate/deliver antigens and TLR agonists such as PolyIC to induce strong antigen-specific CD8+ T cell responses [18,19], our LNPs do not require the encapsulation of TLR agonists or antigen to stimulate strong antigen-specific immune responses [17]. However, the specific requirement for the co-administration of LNPs and antigen and the specific formulation characteristics that dictate the successful generation of strong antigen-specific immune responses by LNPs were not evaluated.…”
Section: Introductionmentioning
confidence: 99%